JURIDICAL ANALYSIS OF THE FULFILLMENT OF THE RIGHTS OF J&T COURIERS WHO EXPERIENCE WORK ACCIDENTS UNTIL DEATH BASED ON LEGISLATION - Nur Aini, Riska Sabilatul; Supriyanti, Supriyanti; Fawwaz, Aqil Ega (Universitas Negeri Surabaya, 2024)
Every job has a level of risk that can have an impact in the form of disability or loss of life triggered by work accidents. Work accidents can occur in industry and can also occur on the way to and from work. The emergence of this risk can not only occur in heavy work but can also occur in workers with low risk levels such as package delivery couriers. This journal will discuss what kind of social security will be obtained by a worker/laborer, which in this case includes a package delivery courier, when he/she has a work accident until death. The research method used in this journal is normative juridical with the use of a statutory approach. The government that has not explicitly presented criminal sanctions for employers who do not register their workers into social security according to existing regulations results in workers who have not fulfilled their rights related to the fulfillment of social security.